MODELING PROCESS OF SYNTHETIC LIQUID HYDROCARBONS FUEL PRODUCTION BY COMBINED STEAM-DRY REFORMING OF METHANE OVER Co-CONTAINING MULTICOMPONENT CATALYST - Valishevsky K.А.,; Itkulova S.S.,; Boleubayev E.A., (Academic Scientific Journal of Chemistry, 2019)
The paper is devoted to modeling the stages of a two-step technology proposed by authors for synthetic liquid hydrocarbons (SLH) production from syngas produced by bireforming of methane – combined steam and dry reforming of methane over own developed catalyst. In both processes: bireforming of methane and Fischer – Tropsch synthesis, the samples of the same catalyst containing cobalt, modified by additives of the transition metals of Groups IVth and VIIIth of the Periodic Table and supported on alumina – 5%Co-М1-М2/Al2O3 have been longterm tested (> 100 hours in each process). The obtained experimental results were used as the basis for calculations at modeling the technological circuit for both processes. As software, Aspen HYSYS was used. In the paper, the modeled technological circuits of syngas production by bireforming of methane and production of synthetic liquid hydrocarbons from syngas over the developed catalyst are presented; the material and heat balances obtained at modeling technology are included too.